Percepción de los estudiantes de educación media sobre el clima escolar y manifestaciones del conflicto escolar en una institución educativa pública de Soledad- Atlántico (2015)
This research project was developed to present secondary education students’ perception towards school environment and the hostile behavior within a public institution in Soledad – Atlántico. As a starting point, 266 students from tenth and eleventh grade were taken into account for research purpose, research from a basic and secondary school in Soledad – Atlántico. The utilized methodology took a quantitative approach. During the first phase, a multiple choice survey was applied. The research revealed the students’ perception towards school environment phenomena and violence.